"Progress?...YEC-C-C-H-H!!!" - McWilliams, C.S. (Cimarron, NM Cimarron Legend, 1992)
Article on the new digital technology and have to go from dialing 4 digits in the village of Cimarron to having to dial 7 digits.
Master List Item # 34
File location is in the New Mexico File Cabinets
Keywords: Miller, Leah; Gonzales, Lisa; Heck, Darlene; Verdum, Brandon; Rohsner, Margaret; Cetrulo, Francie; Cimarron Art Gallery; US West; Phone Dialing; Digital Technology; Phone; Cimarron, New Mexico; Colorado